Advancing the understanding of children’s digital engagement: responsive methodologies and ethical considerations in psychological research - Kucirkova, Natalia; Livingstone, Sonia; Radesky, Jenny (Frontiers in Psychology, 2024)
Children's perspectives and experiences with digital media (digital engagement for short) are becoming difficult to observe and measure in today's highly multi-faceted, personalized and dynamic media ecosystem. In response, psychologists are developing a host of innovative methods. These may be broadly divided into those which prioritize children's active participation in research and those which develop techniques for passive observation. This article presents a state-of-the-art review of emerging methodologies to highlight the ethical issues that arise, by drawing on the Belmont principles for ethical research. We identify strengths and weaknesses of both participatory and non-participatory methods and recommend ways for future research to harness the potential of child-centered, responsive, and ethical methods.